Efficiency in Magnocellular Processing: A Common Deficit in Neurodevelopmental Disorders - Brown, Alyse Christine; Peters, Jessica Lee; Parsons, Carl; Crewther, David Philip; Crewther, Sheila Gillard (Frontiers in Human Neuroscience, 2020)
Several neurodevelopmental disorders (NDDs) including Developmental Dyslexia (DD), Autism Spectrum Disorder (ASD), but not Attention Deficit Hyperactive Disorder (ADHD), are reported to show deficits in global motion processing. Such behavioral deficits have been linked to a temporal processing deficiency. However, to date, there have been few studies assessing the temporal processing efficiency of the Magnocellular M pathways through temporal modulation. Hence, we measured achromatic flicker fusion thresholds at high and low contrast in nonselective samples of NDDs and neurotypicals (mean age 10, range 7–12 years, n = 71) individually, and group matched, for both chronological age and nonverbal intelligence. Autistic tendencies were also measured using the Autism-Spectrum Quotient questionnaire as high AQ scores have previously been associated with the greater physiological amplitude of M-generated nonlinearities. The NDD participants presented with singular or comorbid combinations of DD, ASD, and ADHD. The results showed that ASD and DD, including those with comorbid ADHD, demonstrated significantly lower flicker fusion thresholds (FFTs) than their matched controls. Participants with a singular diagnosis of ADHD did not differ from controls in the FFTs. Overall, the entire NDD plus control populations showed a significant negative correlation between FFT and AQ scores (r = −0.269, p < 0.02 n = 71). In conclusion, this study presents evidence showing that a temporally inefficient M pathway could be the unifying network at fault across the NDDs and particularly in ASD and DD diagnoses, but not in singular diagnosis of ADHD.